2010
DOI: 10.1097/adm.0b013e3181c6cb24
|View full text |Cite
|
Sign up to set email alerts
|

Rural and Urban Differences in Kentucky DUI Offenders

Abstract: : The study suggests that the problem severity among DUI offenders may be greater in rural areas. Given the lack of treatment services in rural areas, practitioners may face greater challenges in assessing and providing appropriate treatment for this group of DUI offenders, which may put them at greater risk for continued impaired driving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 19 publications
2
9
2
Order By: Relevance
“…Aside from prescription drugs, repeat offenders indicated longer periods of regular use for alcohol, marijuana, and illegal drugs overall. These findings are consistent with the limited rural DUI offender literature (Webster et al, 2010). Results also indicate that, similar to urban and national samples of repeat DUI offenders (Hedlund & McCartt, 2002; Wieczorek & Nochajski, 2005), rural repeat DUI offenders have more extensive substance use histories than first time offenders.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Aside from prescription drugs, repeat offenders indicated longer periods of regular use for alcohol, marijuana, and illegal drugs overall. These findings are consistent with the limited rural DUI offender literature (Webster et al, 2010). Results also indicate that, similar to urban and national samples of repeat DUI offenders (Hedlund & McCartt, 2002; Wieczorek & Nochajski, 2005), rural repeat DUI offenders have more extensive substance use histories than first time offenders.…”
Section: Discussionsupporting
confidence: 92%
“…Only a few studies have focused on differences between rural and urban DUI offenders. These studies have found that rural DUI offenders score significantly higher on drug abuse screening instruments and are more likely to 1) have multiple DUI offenses, 2) meet DSM-IV criteria for a substance use disorder, 3) be referred to substance abuse treatment rather than an education intervention, and 4) subsequently be noncompliant with treatment and education recommendations (Webster et al, 2009b; Webster et al, 2010). These findings suggest that problem severity may be greater among rural DUI offenders than urban offenders.…”
Section: Introductionmentioning
confidence: 99%
“…Kirisci and colleagues found severity to be positively related to engaging in risky sexual behaviors. One of the most commonly used measures of problematic drug use is the self-report Drug Abuse Screening Test (DAST; Hormes, Coffey, Drobes, & Saladin, 2011; Mdege & Lang, 2011; Webster, Dickson, Duvall, & Clark, 2010; Yudko, Lozhkina, & Fouts, 2007). The DAST has been shown to be associated with risky sexual behaviors (Kalichman & Cain, 2004; Senn, Carey, Vanable, Coury-Doniger, & Urban, 2006) leading to increased risk of contracting HIV (Ellickson, Collins, Bogart, Klein, & Taylor, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of illicit drug use in this sample highlights the need for thorough clinical assessment for drug use disorders in addition to the alcohol use disorders typically associated with DUI offenders (Maxwell 2012; Webster et al 2010), especially given recent evidence from a national sample of nighttime drivers which found that positive, alcohol breath tests were associated with certain drug use disorders and that a significant proportion of drivers had polysubstance use disorders (Scherer et al 2017). Failing to identify the scope and magnitude of an individual’s substance use problems can limit the effectiveness of treatment.…”
Section: Discussionmentioning
confidence: 96%